What Impact Has Privatization Had on Pay and Employment? A Review of the UK Experience - Pendleton, Andrew (Relations industrielles / Industrial Relations, 1997)
This paper reviews the features and objectives of privatization in the UK. The centrality of labour management and industrial relations objectives to the programme are outlined, with particular attention to the capacity of privatization to reduce political influences on pay détermination and to encourage labour-shedding improvements in efficiency. The paper than considers the available evidence of the effects of privatization on pay and employment. It is found that pay levels have registered above-average increases since privatization. The evidence on employment reductions is more mixed. It is argued that greater product and labour market competition are necessary if the predicted effects of privatization are to be fully realized.